2019
DOI: 10.1088/1748-9326/ab2b53
|View full text |Cite
|
Sign up to set email alerts
|

Association between work in deforested, compared to forested, areas and human heat strain: an experimental study in a rural tropical environment

Abstract: Background: With climate change, adverse human health effects caused by heat exposure are of increasing public health concern. Forests provide beneficial ecosystem services for human health, including local cooling. Few studies have assessed the relationship between deforestation and heat-related health effects in tropical, rural populations. We sought to determine whether deforested compared to forested landscapes are associated with increased physiological heat strain in a rural, tropical environment. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In addition to heat exposure impacts on work productivity, 57,58 heat exposure can cause numerous downstream health impacts. Work in deforested versus forested settings in Indonesia is associated with heat strain, lower cognitive performance, and declines in labor productivity 10,20,31 as well as an increase in all-cause mortality. 32 Individuals working under heat stress are also more likely to experience occupational heat strain and kidney disease or acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to heat exposure impacts on work productivity, 57,58 heat exposure can cause numerous downstream health impacts. Work in deforested versus forested settings in Indonesia is associated with heat strain, lower cognitive performance, and declines in labor productivity 10,20,31 as well as an increase in all-cause mortality. 32 Individuals working under heat stress are also more likely to experience occupational heat strain and kidney disease or acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26]27 Studies on deforestation and temperature changes have focused on quantifying warming from tropical deforestation at regional scales, 13,28 and the relationship between deforestation and increasing temperatures in the tropics is well established. 4,[7][8][9][10][11]29,30 However, only a few small-scale studies have evaluated deforestation effects on heat exposure and the wellbeing of nearby populations in rural communities, 8,31,32 limiting our understanding of whether these effects extend globally in similar settings across low-latitude countries.…”
Section: Introductionmentioning
confidence: 99%
“…The focus on rural communities in tropical countries is important for a few reasons. While studies have long argued for the importance of tropical forests for combating global climate change and biodiversity conservation 14,15 , researchers have more recently started highlighting how tropical deforestation can have significant adverse local human health and well-being impacts [16][17][18][19] . At the same time, the adverse effects of exposure to hotter temperatures are increasingly seen as an area of concern [20][21][22][23][24][25] .…”
mentioning
confidence: 99%
“…48,49 For populations with low adaptive capacity, the relationship between temperature increases and all-cause mortality might be more pronounced, as shown by Lee and colleagues. 35 Recent studies in Berau have found that even under favourable work conditions, working in deforested versus forested areas for just 90 min can result in elevated core body temperatures exceeding 38•5°C 50 and decreased cognitive performance. 51 For outdoor workers engaged in heavy physical activities in the tropics, where heat and humidity are already high, productivity declines can occur with increasing heat stress, as the human body naturally responds to heat stress by triggering reductions in physical work intensity and internal heat generation.…”
Section: Discussionmentioning
confidence: 99%